Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
First.
Calculate f'(x) = (2x/x-1)' = (-2)/[tex] (x-1)^{2} [/tex]; when x is not 1;
Second.
Calculate f'(0) = -2 => the difference quotient (f(a+h)-f(a))/ h, where hod want equal 0 is -2;
Third.
f(a) = 2a/a-1; f(a+h) = (2a+2h)/(a+h-1);
Calculate f'(x) = (2x/x-1)' = (-2)/[tex] (x-1)^{2} [/tex]; when x is not 1;
Second.
Calculate f'(0) = -2 => the difference quotient (f(a+h)-f(a))/ h, where hod want equal 0 is -2;
Third.
f(a) = 2a/a-1; f(a+h) = (2a+2h)/(a+h-1);
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.